AB1213 DIFFERENT IMMUNOSUPPRESSIVE REGIMENS WITH NO EFFECT ON INFLUENZA-LIKE ILLNESS. (13th June 2020) - Freixa, M. I.; Inácio, H.; Amaral, M.; Martins, M.; Costa, C.; Moitinhos, M.; Gruner, H.; Almeitda, A.; Barreto, P.; Pinheiro, S.
Abstract : Background: Autoimmune disease (AID) has been associated with increased risk of influenza and influenza-like illness (ILI) and its worse clinical outcomes complications. Objectives: We aimed to assess the influence and difference of several immunosuppressive (IS) treatments in the incidence of ILI, including glucocorticoids (GC), classic DMARDs and biologic DMARDs. Methods: We conducted a cross-sectional study in two autoimmune clinics. Patients were invited to answer a survey reporting ILI symptoms between October 2017 and March 2018. ILI definition was considered according to the European Center for Disease Control. Data regarding current IS, diagnostic, disease activity, comorbidities, and vaccination coverage were collected from electronic registry. Patients with history of cancer, HIV, IGIV treatment, or lack of information were excluded. Univariate and multivariate logistic regression analysis were used to access predictors of ILI. Results: We included 109 patients, with mean age 51 years and 81% female gender. The majority of patients had autoimmune arthropathy (n=54) or a connective tissue disease (n=44). Active disease was present in in 39% of patients. IS treatment was: GC 31%, classic DMARD 44%, biologic DMARD 28%. Vaccine coverage was 51%. Overall 41% reported ILI. We did not find any association between studied variables and ILI, including univariate and multivariate analysis. Univariate odds ratio calculation for IS treatment were: GC [OR 1, 68 IC 0, 7-3, 8], classic DMARD [OR 1, 03 IC 0, 5-2, 2], and biologic DMARD [OR 0, 86 IC 0, 4-2, 0]. Comorbidity of pulmonary disease (n=8) may contribute to higher risk to ILI [OR 2, 76 IC 0, 8-10, 0]. Conclusion: There was no difference in risk of ILI within different IS treatment regimens, although GC may increase the risk. The study is limited by the subjectivity of the ILI survey and the small size of the sample. The stratification of influenza risk will help in designing better vaccine coverage strategies in this population. References: [1]Nakafero G, Grainge MJ, Myles PR, Mallen CD, Zhang W, Doherty M, Nguyen-Van-Tam JS, Abhishek A. Predictors and temporal trend of flu vaccination in auto-immune rheumatic diseases in the UK: a nationwide prospective cohort study. Rheumatology (Oxford). 2018 Oct 1;57(10):1726-1734. [2]Danza A, Ruiz-Irastorza G. Infection risk in systemic lupus erythematosus patients: susceptibility factors and preventive strategies. Lupus. 2013 Oct;22(12):1286-94. [3]McLean-Tooke A, Aldridge C, Waugh S, Spickett GP, Kay L. Methotrexate, rheumatoid arthritis and infection risk: what is the evidence? Rheumatology (Oxford). 2009 Aug;48(8):867-71. [4]Lacaille D, Guh DP, Abrahamowicz M, Anis AH, Esdaile JM. Use of non biologic disease-modifying antirheumatic drugs and risk of infection in patients with rheumatoid arthritis. Arthritis Rheum. 2008 Aug 15;59(8):1074-81. [5]Bernatsky S, Hudson M, Suissa S. Anti-rheumatic drug use and risk of serious infections in rheumatoid arthritis. Rheumatology (Oxford). 2007 Jul;46(7):1157-60. [6]Doran MF, Crowson CS, Pond GR, O'Fallon WM, Gabriel SE. Predictors of infection in rheumatoid arthritis. Arthritis Rheum. 2002 Sep;46(9):2294-300. [7]Fessler BJ. Infectious diseases in systemic lupus erythematosus: risk factors, management and prophylaxis. Best Pract Res Clin Rheumatol. 2002 Apr;16(2):281-91. Review. [8]Singh JA, Wells GA, Christensen R, Tanjong Ghogomu E, Maxwell L, Macdonald JK, Adverse effects of biologics: a network meta-analysis and Cochrane overview. Cochrane Database Syst Rev. 2011 Feb 16;(2):CD008794. Acknowledgments: None. Disclosure of Interests: None declared